Peningkatkan Hasil Belajar Melalui Audio Visual dalam Materi Iman kepada Malaikat pada Peserta Didik - Sarni Sarni; Yusmarinda Yusmarinda; Erlida Erlida (Jurnal Manajemen dan Pendidikan Agama Islam, 2023)
This study aims to improve students' learning outcomes regarding the material of faith in angels through the use of audiovisual media. This media refers to a learning strategy that utilizes sound and image elements, so that in the process of absorbing the material, students can involve their senses of sight and hearing. This Classroom Action Research (CAR) was carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through observation, practical tests, and interviews, then analyzed descriptively. The results of the study showed a significant increase in students' understanding of the material of faith in angels after the application of audiovisual media. In the first cycle, many students still had difficulty understanding the material. However, in the second cycle, a significant increase in the accuracy of their understanding was observed. Thus, the application of the audiovisual method has proven effective in improving students' skills in understanding the meaning of faith in angels.